2014
DOI: 10.1186/1475-9276-13-52
|View full text |Cite
|
Sign up to set email alerts
|

The impact of economic crises on social inequalities in health: what do we know so far?

Abstract: Since 2008, Western countries are going through a deep economic crisis whose health impacts seem to be fundamentally counter-cyclical: when economic conditions worsen, so does health, and mortality tends to rise. While a growing number of studies have presented evidence on the effect of crises on the average population health, a largely neglected aspect of research is the impact of crises and the related political responses on social inequalities in health, even if the negative consequences of the crises are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 32 publications
4
79
0
5
Order By: Relevance
“…Indeed, some authors have shown that the relationship between the changes in the structural determinants and health inequalities is complex [44,45]. According to our results, the improvement of the socioeconomic indicators and the increase of social inequalities in disability and disability-free life expectancy in men occurred simultaneously.…”
Section: Discussionsupporting
confidence: 63%
“…Indeed, some authors have shown that the relationship between the changes in the structural determinants and health inequalities is complex [44,45]. According to our results, the improvement of the socioeconomic indicators and the increase of social inequalities in disability and disability-free life expectancy in men occurred simultaneously.…”
Section: Discussionsupporting
confidence: 63%
“…However, efforts to reduce inequalities have not been stronger in Italy than in other countries 4. Other structural developments may have undone the effects of policies on health inequalities such as the economic recessions in some European countries in the early 1990s and the late 2000s,41 increases in income inequalities (eg, England),20 42 and changes of working conditions (eg, more work-related stress) 21. Nevertheless, the observed trends of inequalities in SAH are not consistent with the amount of effort made to reduce health inequalities in some countries.…”
Section: Discussionmentioning
confidence: 96%
“…Since 2007, the economic scenario has worsened as Portugal faced severe consequences of the global economic/financial crisis 36. Experience and evidence from past recessions show a negative impact of austerity policies on heath inequality 37. Recession periods can impact people’s lifestyles in several ways, which in turn might affect long-term HF rates, although we would expect that such an impact would reflect smooth changes in the trends of HF.…”
Section: Discussionmentioning
confidence: 97%